Deteksi Plat Nomor Kendaraan Bermotor dengan Segmentasi Gambar - Yasinta Oktavina Legu Rema (Fakultas Pertanian, Universitas Timor, 2019)
A lot of system with many various for plate recognition in other country and methods. This application is used to detect plate of vehicle based on image data form. It can help a bigger system that used for plate identification. Input that used is image file. The application will show user an input in image form and process it using image segmentation. Image segmentation will extract object from image that will not use and dividing an image into multiple parts. Before find the plate, application will processing image to get a better quality image with many ways including RGB and grayscale processing, image resize, area calculation, edge detection and segmentation. And the output will be view in image file.